Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
ZenodoArchiveID: 4556932 PreviousDOI: 10.5281/zenodo.4477141 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948149 10.5281/ZENODO.4556932 10.5281/zenodo.4477141 10.5281/zenodo.4556932 2259720:DSXFK6JB 2339240:4JRWSL6I 2339240:8YVF7D5N 2339240:EPCMUN8C 2339240:FKFII8IK 2339240:H8YNQIY9 2339240:IJJ6TY76 2339240:QBDJ6U43 2339240:YIAFCN9T 2405685:5GBRDVHP 2405685:65UPSCK3 2405685:67BFM4C5 2405685:6CG6479A 2405685:DM6JSS9K 2405685:P8NUYK3M 2405685:PZHGV2XR 2405685:QBYZW7N2 2405685:RBUXXHAD 2405685:VHGNZV9N 2405685:X8BFH2K5 2405685:YMWE6FR6
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15366685 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1113 ZenodoArchiveConcept: 15366684
Keywords: _r:AddedByMyEducationEvidence